Uso de antidepressivos e ansiolíticos por pacientes atendidos em Unidades Básicas de Saúde em um município da Amazônia Brasileira - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2024)
In this article, we investigated the distribution of anxiolytics and antidepressants in Basic Health Units in Santarém-PA, in the Amazon region. Data was collected from 41 patients, through questionnaires administered in nine units. The analysis revealed the real situation of the distribution of these medicines and highlighted the absence of pharmaceutical professionals to deal with possible problems related to the use of medicines, showing that their role in primary care is still limited in the municipality. Furthermore, there was a lack of medication for low-income patients who need treatment for anxiety and depression, but do not have the resources to purchase them. Another aspect observed is that the delivery of medications by other health professionals can result in treatment failures due to the lack of specialized monitoring of pharmacotherapy.
Keywords: Antidepressivos; Ansiolíticos; Atenção Primária à Saúde; Farmacêutico; CNPQ:: CIÊNCIAS DA SAÚDE